Perjanjian Kredit Hak Cipta Sebagai Obyek Jaminan Fidusia di Kota Medan - Tarmizi Tarmizi (Penelitian dan Pengembangan Ilmu, 2024)
Banks as banking institutions require collateral (collateral) in providing credit to the public, and until now fiduciary is the type of guarantee binding that is most in demand by the people of Indonesia. Provisions of Law No. 28 of 2014 concerning Copyright, namely Article 16 paragraph 3 states that